TRANSITION TO GREEN ECONOMY IN UZBEKISTAN – A PATH TO SUSTAINABLE DEVELOPMENT - Choriyevich, Khidirnazarov Sirojiddin (American Journal of Biology and Natural Sciences, 2025)
The transition to a green economy directs Uzbekistan’s economic development model toward an environmentally sustainable and innovative path. This shift plays a crucial role not only in protecting the environment but also in creating new jobs and increasing energy efficiency. This article analyzes the relevance of the green economy transition in Uzbekistan and the development processes in this area. Particular attention is given to key objectives of the green economy such as the efficient use of natural resources, ensuring environmental safety, improving energy efficiency, and widely implementing innovative technologies. The article also provides analytical data on the priority directions, implementation mechanisms, and expected outcomes of the Green Economy Development Strategy for 2019–2030. It highlights the importance of adhering to sustainability principles and maintaining ecological balance in Uzbekistan’s economic development.